2017
DOI: 10.47197/retos.v0i34.50748
|View full text |Cite
|
Sign up to set email alerts
|

Factores motivacionales relacionados con la intención de seguir practicando ejercicio físico en mujeres adultas (Motivational factors related to the intention to continue practicing exercise in adult women)

Abstract: El objetivo principal del estudio fue analizar la influencia de la satisfacción de las necesidades psicológicas básicas y los diferentes tipos de motivación sobre la intención de seguir practicando ejercicio físico en mujeres adultas. Se utilizó una muestra de 145 practicantes cuya edad media fue 48.03. Todas las participantes eran practicantes de actividades físicas dirigidas en distintos centros deportivos públicos de Huelva. Se midieron las necesidades psicológicas básicas en el ejercicio, los diferentes ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…Barriers and facilitators should be openly discussed at the initial assessment of the intervention and at subsequent intervals to improve the individualization of exercise prescription ( 41 ). Follow the self-determination model ( 11 ) and promote self-determined forms of motivation that have shown greater adherence to physical exercise ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers and facilitators should be openly discussed at the initial assessment of the intervention and at subsequent intervals to improve the individualization of exercise prescription ( 41 ). Follow the self-determination model ( 11 ) and promote self-determined forms of motivation that have shown greater adherence to physical exercise ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Al respecto, Edmunds et al (2006a) y González-Cutre y Sicilia (2012) encontraron que la regulación introyectada comparte pequeñas correlaciones negativas o no significativas con la satisfacción de las necesidades psicológicas básicas en las personas que hacen ejercicio. En cambio, estos resultados contrastan con los hallados por Bermejo et al (2018), quienes encontraron que la regulación identificada predijo significativa y positivamente la intención de seguir practicando EF a pesar de la presencia de lesiones o enfermedades, lo que puede deberse a los sentimientos eufóricos y aspectos gratificantes que genera el EF y pueden conducir al desarrollo de un comportamiento desadaptativo (Weinstein & Weinstein, 2014), por lo que es necesario seguir estudiando la relación de las variables de la MD en relación a la dependencia del EF, para poder esclarecer qué aspectos de la motivación son más relevantes para explicar este fenómeno.…”
Section: Discussionunclassified
“…Similarly, studies have shown there is a relationship between the practice of PA and more self-determined motivation DeFreese and Smith, 2013). The scientific literature supports the idea that more self-determined motivation is decisive to achieve greater beneficial effects from PA, such as control of body weight, increased physical fitness, positive improvement in mood, among others (Moreno-Murcia et al, 2011;Bermejo et al, 2018;. Studies by Durán-Vinagre et al (2021) and Lauderdale et al (2015) showed that there are statistically significant differences between men and women in terms of intrinsic motivation, integrated regulation and identified regulation.…”
Section: Introductionmentioning
confidence: 87%